Tetrapod breakwaters stability under breaking wave conditions - Çevik, E; Yuksel, Y (INTERNATIONAL SOCIETY OFFSHORE& POLAR ENGINEERS, 2003)
Many of rubble mound breakwaters in the world armored with artificial unit. Tetrapod is one of the artificial units. One area of interest has been the effect of the armoring unit placement method on the stability of breakwaters. The tetrapod stability for two different placement methods under regular wave attack under breaking wave conditions is the subject of this paper. The paper presents the results of the laboratory tests of the stability of two placement methods.
Keywords: breakwater; tetrapod; breaking wave; stability; Engineering; Oceanography